PSXVII-27 Effect of 25-hydroxy-vitamin-D3 on feedlot cattle. (7th December 2018) - Sabella Acedo, T; Nunes de Gouvea, V; de Souza Floriano Machado de Vasconcellos, G; Arrigoni, M; Ludovico Martins, C; Millen, D; Rosolen Muller, L; Fernandes de Melo, G; Argentini Rizzieri, R; Floret da Costa, C; Domingues Sartor, A
Abstract: The objective with this experiment was to evaluate doses of 25-hydroxy-vitamin-D3 on average daily gain (ADG), dry matter intake (DMI), feed efficiency (F:G) and dressing percentage (DP) in finishing beef cattle. A total of 120 Nellore bulls (IBW = 375 ± 24 kg) distributed in 24 pen (5 animals/pen) were used in a randomized complete block design (8 pens/treatment). The dietary treatments were: 1) control (CON): no supplementation of 25-hydroxy-vitamin-D3, 2) HyD1: 25-hydroxy-vitamin-D3 supplementation at 1 mg/animal/d and 3) HyD3: 25-hydroxy-vitamin-D3 supplementation at 3 mg/animal/d. The basal diet was formulated to meet the requirements of finishing bulls to a ADG of 1.6 kg (Level 2 Nutrition System, Fox et al., 2004) and it was composed of 13% forage and 87% concentrate (DM basis). The animals were fed twice a day at 08:00 (40% of the total) and 15:00 (60% of the total). The pens were fully covered, protecting feed from the sun and rain, with good air circulation. At the beginning and end of the experimental period the animals were weighed without fasting for two consecutive days. The initial and final body weight was calculated by the average of the two days discounting 4% to obtain the lean weight. Statistical analysis was performed using the PROC MIXED procedure of SAS (2003) and means comparison evaluated by Tukey test at 10% probability. HyD supplementation did not change the final body weight (513.0 kg), ADG (1.43 kg/d), DMI (9.8 kg/d) and FE (0.145) (P > 0.10). Nevertheless, feeding HyD at 1 mg/d increased the dressing percentage of the animals compared to the control group (56, 46 vs 55, 92%; P = 0.063). In conclusion, HyD supplementation can be used as a tool to increase carcass yield in finishing cattle. Key Words: